The industrial ghosts of the past and an approach to the pragmatic dimension of semiosis. the case of the Pilsen Trujillo Beer factory, La Libertad, Peru - Velásquez García, Juan (2021)
The objective of this research was to unveil the the values of industrial cultural heritage, specifically, the Pilsen Trujillo beer Factory in La Libertad, Peru. This issue was seen from the perspective of the pragmatic dimension of semiosis. Nowadays, in Peru the industrial buildings are disregarded by the cultural heritage institutions. This research was qualitative because it was conducted to discover cultural meanings, which belong to the industrial cultural heritage from the perspective of the users. Finally, the evidences led to the conclusion that heritage objects, as the Pilsen Trujillo beer factory, have communicational attributes. Therefore, semiosis, especially the pragmatic dimension, is necessary to comprehend the relation between a heritage object and its users.